2015
DOI: 10.4236/jbnb.2015.64026
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Chitosan Films Obtained after Neutralization of Polycation by Slow Drip Method

Abstract: The development of new materials from biodegradable constituents is enticing for applications in bioelectronics and biomedicine, due to their considerable durability, versatility and biodegradability. The present work aims to determine the chemical and physical properties of chitosan membranes after neutralization of the polycation solution. This work was divided into two stages: solubilization and neutralization. In the first stage, the chitosan was solubilized with three different concentrations of acetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Elongation-at-break of Chitosan films alone and after the addition of Silica Nanoparticle and nisin exhibited greater resistance to the strain. Llanos et al [ 13 ] reported high values among Chitosan films in stress tests due to the porosity of the membranes. Chitosan/Silica Nanoparticle films showed a higher strain of 12.49% compared with Chitosan/Silica Nanoparticle/N films at 5.25%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elongation-at-break of Chitosan films alone and after the addition of Silica Nanoparticle and nisin exhibited greater resistance to the strain. Llanos et al [ 13 ] reported high values among Chitosan films in stress tests due to the porosity of the membranes. Chitosan/Silica Nanoparticle films showed a higher strain of 12.49% compared with Chitosan/Silica Nanoparticle/N films at 5.25%.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility of the films in water was evaluated according to the method by Lianos et al [ 13 ]. The film samples were cut into (2 × 6 cm) and were stored in a desiccator with P2O5 (0% RH) for 72 h. Dry films were weighed to the nearest 0.01 g, immersed in phosphate buffer solutions with respective (pH = 5.9), and stirred for 1 h at the ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the amine group in chitosan has a p K a of 6.3; hence, Cs remains soluble at weakly acidic solutions. 24 In the present case, the metal chelation testing was done in the artificial sweat solution (EN 1811:2011) at pH 6.5 considering that the applied gel will encounter only sweat on practical application.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of Aloe vera was performed manually with a glass stick. All formulations were neutralized by slow drip of neutralizing solution (NaOH, 2M) at the rate of one drop of solution per minute (1 drop/minute) until reaching a pH of ≈ 7.0 under constant agitation (50 rpm), a methodology adapted from Llanos et al (2015). The organoleptic analysis of the gels was performed to evaluate the characteristics detectable by sight and smell.…”
Section: Methodsmentioning
confidence: 99%